Pemberdayaan Masyarakat Desa Rabak dalam Memanfaatkan Limbah Sekam Padi sebagai Media Tanam Sayuran - Nurhasanah Nurhasanah; Sri Harijati; Ludivica Endang Setijorini; A. Hadian Pratama Hamzah; Hasrianti Hasrianti; Aji Marwonto Aris Munandar (Jurnal Surya Masyarakat, 2025)
This study addresses the utilization of rice husk waste as a planting medium to promote vegetable cultivation in household gardens, aiming to reduce household expenses and improve the nutritional health of Desa Rabak residents. The rice husk, a common agricultural byproduct, enhances soil structure, aeration, and nutrient availability, supporting sustainable agricultural practices. The community engagement program (PkM) was conducted on October 15, 2024, involving 26 residents, including the village farmer group leader, and a team from Universitas Terbuka. Activities included theoretical explanations about rice husk benefits, practical demonstrations of organic liquid fertilizer application, distribution of coffee and fruit seedlings, and awarding prizes for active participation. Participants also received education on vegetable gardening techniques and the benefits of consuming self-cultivated produce. The program demonstrated significant potential for sustainable farming practices by transforming waste into productive resources, leading to reduced household expenses and enhanced community health. Moreover, it fostered community awareness of Universitas Terbuka's educational opportunities. Future initiatives are recommended to include advanced training on post-harvest management and involve broader stakeholder participation to maximize economic and social impacts.